Vanishing Point: an art/science collaboration and exhibition on the impact of microplastics in our oceans - Heidi Auman; Peter Walsh; Patti Virtue; Frederique Olivier; Carnell, S; Cooper, K; Masters, D; Mausz, G; Muir Wilson, T (2019)
THE PROJECT. Vanishing Point is an arts/science collaboration to raise awareness about the issues surrounding plastics pollution in the oceans and its ecological, biological and social impact. Initially the brainchild of wildlife artist Katherine Cooper, in 2015 Vanishing Point’s first exhibition was held at the Institute for Marine and Antarctic Studies. Katherine was joined by four other artists (Peter Walsh, Ron Moss, Toby Muir-Wilson and Sophie Carnell) and three scientists (Heidi Auman, Patti Virtue and Frederique Olivier) from the Institute for Marine and Antarctic Studies (IMAS, in Hobart, Tasmania) researching impacts of ocean plastics. The goal of the project was to raise awareness in the community about the impact of our daily use of plastics through art and science communication in a complementary and engaging manner. The 2017 exhibition included the work of two new artists, Di Masters – Multi Media Artist and - and Gerhard Mausz - sculptor and designer. The exhibition expanded on the 2015 project by embracing the theme of Unseen. From micro-beads in personal care products, microfibres in synthetic clothing, and fragments derived from the breakdown of larger debris, micro-plastics are increasingly invading our marine systems and food chains. This is now recognised as a serious global environmental issue. THE SCIENCE. "As many as 51 trillion microplastic particles - 500 times more than stars in our galaxy - litter our seas, seriously threatening marine life." - United Nations report An estimated 5-13 million metric tons of plastic end up in our oceans each year. Microplastic debris begins the journey to the sea as consumer and industrial products like exfoliants, cosmetics and industrial abrasives, or breakdown of larger plastic items. Even synthetic fibres shed from our clothes during washing contribute to this unseen but now widespread marine pollution. Microplastics can affect wildlife in many harmful ways. Ingestion and physical obstruction can reduce feeding by marine life and lead to starvation. ...